MODERATE ISLAMIC VALUES TO ENHANCE NATIONALISM BETWEEN MUHAMMADIYAH ORTOM (CASE STUDY: IKATAN MAHASISWA MUHAMMADIYAH, EAST JAKARTA) - Ahmad Ruslan; Hari Naredi; Herdin Muhtarom; Ratih Anggie Wardani; Khoiriah Khoiriah (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
The development of the era and the threat of globalization have the potential to threaten youth because the psychological condition of youth is still unstable so that they are easily influenced from outside. Today's youth are very easily affected by the effects of westernization so that in an instant they can change the values that have been held so far. This will affect the values of nationalism among youth in Indonesia. The aim of this research is to find out moderate Islamic values to increase nationalism among Muhammadiyah autonomous circles (case study; Muhammadiyah Student Association, East Jakarta). The method used in this research is to use a qualitative descriptive research model with a case study approach model.